A COMPARISON OF LIVING STANDARDS ACROSS THE UNITED STATES OF AMERICA. (4th October 2022) - Falcettoni, Elena; Nygaard, Vegard M.
Abstract: We use an expected utility model to examine how living standards, or welfare, vary across the United States and how each state's welfare has evolved over time, accounting for cross‐state variations in mortality, consumption, education, leisure, and inequality. We find considerable cross‐state heterogeneity in welfare levels. This is robust to allowing for endogenous interstate migration and to computing welfare conditional on education, gender, and race. Although states experienced heterogeneous welfare growth rates between 1999 and 2015 (1.68–3.73% per year), there is no evidence of convergence in welfare levels, including during the subperiods preceding and following the Great Recession.